(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Introduction: Hypertension (HTN) is defined as a clinic (office) systolic blood pressure ≥140 mm Hg and/or diastolic blood pressure ≥90 mm Hg. It is common, but if left untreated, it can be serious. HTN is classified as primary or secondary. High blood pressure is a disorder that damages blood vessels by forcing blood against the walls of the arteries. The circulatory system will be under greater stress, which raises the chance of cardiac conditions such as stroke, aneurysm, and congestive heart failure, as well as other conditions including renal issues, retinal hemorrhage, metabolic syndrome, and dementia. There has been a growing worry worldwide over the rise in teenage and young adult HTN cases, which go undiagnosed due to insufficient screening in that age group. We are conducting this study due to insufficient number of researches related to our topic, especially in Saudi Arabia. Objective: The study aimed to assess the respondents’ family history of HTN and its associated risk factors from dietary triggers among the Saudi population. Materials and Methods: This was a cross-sectional study. This study, which conducted from July 2024 to February 2025, uses an online questionnaire to assess the prevalence of HTN and its associated risk factors (dietary among patients in Saudi Arabia). The study plans to recruit participants through an online questionnaire. The inclusion criteria for this study were as follows: All Saudi males and females over 18 years. Non-Saudis, <18 years, were excluded from this study. The minimum target sample size is 384, which was calculated using a formula based on prevalence estimation, 95% confidence level, and 5% acceptable error. Results: The study assessed the family history of HTN and associated dietary risk factors among 460 Saudi participants, with a mean age of 37.9 years. A significant 60.2% reported a family history of HTN, highlighting genetic predisposition. Dietary habits revealed concerning trends: 30.7% consumed white rice daily, while 45% reported daily intake of high-salt foods, both linked to HTN. Caffeinated drink consumption was high, with 60.4% drinking them daily. Notably, a lack of engagement with health-oriented beverages such as green tea and hibiscus was evident,